Innovations in computer science and engineering - Halt, Tom (Wiilford Press, 2016)
Rapid technological changes have led to new innovations in computer science and engineering. The ever growing need for advanced technology has fueled the research in the fields of computing, signal processing and embedded systems. This book examines various studies that are constantly contributing towards advancing technologies and brings forth new areas for future research. This book is an attempt to provide in-depth knowledge about the theory and practice of mobile computing, robotics and industrial electronics. It will provide comprehensive knowledge to the readers.